A framework for using computational fire simulations in the early phases of ship design. (1st January 2017) - Kang, Hee Jin; Choi, Jin; Lee, Dongkon; Park, Beom Jin
Abstract: Fires on ships spread rapidly and are difficult to control. Both passengers and some ship crew maybe unfamiliar with real fire situations. Mismanagement or a delayed preliminary response can yield fatal damage to a ship, including the loss of lives. Despite all ships being built in accordance with to fire safety rules and regulations, ship fire accidents still occur. Currently, computational simulation tools are used to predict and mitigate fire propagation during the ship design process. Dynamic fire simulations can assist better appreciation of heat and smoke tendencies and behavior based on cause, location and environmental conditions. Moreover, ship designers can apply fire control options, such as fume-tight doors, sprinklers, water mist while giving due consideration for improved survivability. However, fires have no reproducibility, and many types of equipment and facilities cannot be considered in such simulations. In addition, applying the simulation is sometimes difficult because the design process is typically limited by budget and time constraints. Numerous fire scenarios are required for accurate simulations. Vague and varying simulation requirements can confuse ship designers. Consistently decreasing design freedom and major design revision requirements can cause projects to fail. Therefore, a framework for using computational fire simulations during the early phases of ship design was explored in this study. This work is focused on how to arrange fire control options with minimal changes of existing design procedures. Highlights: A framework organized within the bounds of existing rules and regulations. for performing computational fire simulations during early ship basic design phase. that does not require substantial changes to design processes, is presented. The framework can be adopted even in the absence of all the required design input data. The above can also be considered for life cycle fire safety management.